Analisis Sistem Informasi Akuntansi Pemberian Kredit Pada Koperasi Simpan Pinjam Putra Surya Mandiri Mojosari Mojokerto - Naimah, Alful Laili; Dewianawati, Dwi; Rahayu, Sari (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2023)
This study aims to find out how the accounting information system for granting credit in the Putra Surya Mandiri Mojosari Mojokerto Savings and Loan Cooperative. The method used in this study is a qualitative method with data collection techniques in the form of interviews, documentation and observations. Based on the results of the research obtained, the procedure of the accounting system for granting credit at the Putra Surya Mandiri Mojosari Mojokerto Savings and Loan Cooperative is effective, namely it is found with the documents used, accounting records used, related functions and credit granting procedures that are appropriate and structured with applicable provisions. However, the settlement of credit provision has not met the documents used, namely there is no power of attorney to sell used to sell collateral in the event of bad credit. And the assessment of credit provision at the Putra Surya Mandiri Mojosari Mojokerto Savings and Loan Cooperative is only carried out by the Surveyor, the absence of a Financing/Loan Analysis section makes the results of the analysis can be engineered by the surveyor.